Pengembangan Media Interaktif Berbasis Kontekstual Berbantuan Mentimeter dalam Pembelajaran Daring pada Mata Pelajaran Ekonomi - Handika Madya Ramadhani Putra; Eka Hendi Andriansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
The existence of distance learning activities causes the learning process to be obstructed. Less appropriate use of media will be able to impact on the learning outcomes of learners due to the lack of optimal level of availability of learning materials. The purpose of this study is to know the process of media development itself, describe the feasibility of the media, as well as the response of learners, and the learning outcomes of learners after the use of Mentimeter. This study uses a type of research and development research with the subjects studied are students of XI IPS SMA Labschool Unesa. Results showed that development results of using Mentimeter generated positive feedback from learners. Learners are aroused by their interest and motivation in learning Economics thanks to the ease of use and content listed in the media. Utilization of contextually assisted contextual learning media Mentimeter is also fairly effective in learning seen from the significant improvement of learners' learning outcomes.